HOW ARE CHILDREN AND YOUNG PEOPLE ENGAGED IN RESEARCH ON PAEDIATRIC OBESITY AND WHICH ISSUES DO THEY REPORT? A SCOPING REVIEW - Concincion, Siegnella; van Houtum, Lieke; van de Vorst, Birgitta; Verhoeff, Arnoud; Dedding, Christine (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2023)
The importance of engaging children and adolescents in research is increasingly acknowledged. The aim of this scoping review is to explore how children and young people have been engaged in research on paediatric obesity and which issues they have reported, in order to highlight areas that require further inquiry or action by researchers and health care professionals. There were 13 papers eligible for this review. Methods used included in-depth interviews, structured or semi-structured interviews, and focus groups, as well as more creative qualitative research methods. Half of the studies included young people with their parents; parents were always present when the interviewees were young children. Personal and sensitive themes, such as bullying, a desire to “fit in”, strong negative emotions about oneself (e.g., low self-esteem, low self-efficacy), and not feeling supported by family, peers, and professionals, were more often shared if parents were not present. An additional issue, wanting to be independent versus being under parental control was found in studies with adolescents. Engaging children and adolescents in multiple phases of research on paediatric obesity is beneficial in allowing better insight into their perspectives and providing recommendations that are more in line with their personal needs and life circumstances; such studies are still scarce in this field, however.